Adverse selection in mortgage securitization - Agarwal, Sumit; Chang, Yan; Yavas, Abdullah (Journal of Financial Economics, 2012)
Using several large data sets of mortgage loans originated between 2004 and 2007, we find that in the prime mortgage market, banks generally sold low-default-risk loans into the secondary market while retaining higher-default-risk loans in their portfolios. In contrast, these lenders retained loans with lower prepayment risk relative to loans they sold. Securitization strategy of lenders changed dramatically in 2007 as the crisis set in with most unwilling to retain higher-default-risk loans in return for lower prepayment risk. Contrary to the prime market, the subprime market does not exhibit any clear pattern of adverse selection.